Suran Tradition as A Tourism Attraction in Traji Village : A Continuous Tradition of Welcoming the Javanese New Year - Hapsari, Notriska Karumetta; Subandi, Agus; Mugiyo, Mugiyo (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
The customary practice of suran in Traji Village serves as a traditional means of welcoming the Javanese New Year, which typically occurs during the month of Suro, corresponding to the 1st of Muharram in the Hijri calendar. The Sendang Sidhukun tourist site in Traji Village features a customary bridal procession ritual conducted for the benefit of rice fields. This location serves as a vital source of irrigation for farmers in Traji Village. This tradition imparts its own charm to the tourism industry in Sendang Sidhukun. This study utilized a qualitative research methodology using a case-study approach. The results of this study show that the Suran tradition in Traji Village has been practiced continuously since antiquity and has been transmitted from one generation to the next. This tradition started to thrive with the emergence of a water source in 1443, now known as Sendang Sidhukun. This tradition has contributed to the development of Sendang Sidhukun as a tourist destination. As a result, both the community and village administration employ the suran tradition as a tourist attraction, emphasizing the singularity of Javanese customs in terms of attire, rituals, and shadow puppet performances.